Stroke: Just a Chemistry: - Torabi-Nami, Mohammad (Galen Medical Journal, 2016)
Stroke is a significant health issue with its neuropathological mechanisms requiring better understanding. Within the course of ischemic stroke, obstruction of a major brain artery results in an abrupt blood flow limitation below a critical threshold and focal ischemic brain insult arises. Chemical shift imaging using magnetic resonance spectroscopy and more advanced imaging methods have recently provided some novel insights into the chemistry of stroke. Given the fact that stroke disturbs the normal brain chemistry, assessing and perhaps targeting the metabolic pathways ought to be a practical and useful approach to better understand the neurobiochemical aspects of stroke. This perspective paper focuses on the evolving dimensions of neurochemical research in stroke.[GMJ.2016;5(2):49-55]